AVIATION BUSINESSES DURING COVID-19: AIRASIA'S FINANCIAL CHALLENGES AND POSSIBLE WAY-OUTS (Al Dzahab, 2024)
Purpose: This paper aims to discuss the financial challenges faced by AirAsia and the possible way-outs in the wake of the company’s slumped performance caused by COVID-19.Design/methodology/approach: The methods used are qualitative, in-depth company studies and articles.Findings: The result of this study can be concluded that AirAsia has several financial challenges that the analysis can see of the company’s finances. AirAsia also strives to implement several strategies to cope with COVID-19’s impact despite enormous and competing challenges and uncharted solutions.Research implications: This article provides an overview of the strategy implemented by AirAsia after experiencing a downturn due to the COVID-19 pandemic.